The Development of Scientific Concepts about Refraction of Mathayomsuksa 5 Students Using Predict-Observe-Explain with Interactive Simulation Media.: Scientific Conceptual, Predict-Observe-Explain Learning Method, Science Process Skills, Interactive Simulation Media - Joysriket, Nattapong; Wongwanwattana, Pakawat; Jomhongbhibhat, Bhumbhong (Ubon Ratchathani Journal of Research and Evaluation, 2024)
This research aimed to 1) develop the student’s scientific conceptual understanding of the Refraction of Light for Mathayomsuksa 5 students by using Predict-Observe-Explain (POE) method with interactive simulation media. 2) Study scientific skills of students after learning by using POE method with interactive simulation media. 3) To assess student’s satisfaction in activities. The target group were 41 students form Mathayomsuksa 5 in Phibunmangsahan School. Six lesson plans were constructed and used following the POE method. The data were collected by the conceptual test, before and after the implementation of the lesson plans consisting of 12 items in Three-Tier Multiple Choice test. Scientific process skills assessment form and Satisfaction questionnaire. The data were analyzed using the Mean, Standard deviation, Percentage and t-test statistics. The research findings were as follows: Measurement of understanding of scientific concepts was conducted before and after the intervention showed average scores before and after the intervention were 22.33 and 80.89. when comparing before and after intervention scores, a statistically significant difference was found, with the after intervention scores being significantly higher at a significance level of .05 Students demonstrated good overall science process skills, including prediction, observation, and interpretation with an average score at the high level ( =2.46, SD=0.34) The student’s satisfaction in POE with interactive simulation media the overall was at the high level ( =4.36, SD=0.23)